Engineering of TMDC-OSC Hybrid Interfaces: The Thermodynamics of Unitary and Mixed Acene Monolayers on MoS2 - Kachel, Stefan R.; Dombrowski, Pierre Martin; Breuer, Tobias; Gottfried, Michael; Witte, Gregor (ChemRxiv)
Here, we use temperature-programmed desorption (TPD) and Monte Carlo (MC) simulations of TPD traces to characterize the desorption kinetics of pentacene (PEN) and perfluoropentacene (PFP) on MoS2 as a model system for OSCs on TMDCs. We show that the monolayers of PEN and PFP are thermally stabilized compared to their multilayers, which allows to prepare nominal monolayers by selective desorption of multilayers. This stabilization is, however, caused by entropy due to a high molecular mobility rather than an enhanced molecule-substrate bond. Consequently, the nominal monolayers are not densely packed films.